2016
DOI: 10.1074/jbc.m116.730358
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of Isopropylmalate Dehydrogenase from Arabidopsis thaliana

Abstract: Isopropylmalate dehydrogenase (IPMDH) and 3-(2-methylthio)ethylmalate dehydrogenase catalyze the oxidative decarboxylation of different ␤-hydroxyacids in the leucine-and methionine-derived glucosinolate biosynthesis pathways, respectively, in plants. Evolution The evolution of specialized metabolic pathways from primary metabolism provides plants with the ability to generate molecules that contribute to their survival (1). The classic cycle of gene duplication and divergence of sequence that leads to new sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Protein Expression and Purification. The general protein expression and purification protocol for UGT76G1 uses a combination of affinity and sizeexclusion chromatographies based on a previously published protocol (32). For production of SeMet-substituted protein, the pET-28a-UGT76G1 construct was transformed into E. coli BL21 (DE3) cells, which were grown to A 600 ∼ 0.8 at 37°C in M9 minimal media supplemented with SeMet containing 50 μg·mL −1 kanamycin (33).…”
Section: Methodsmentioning
confidence: 99%
“…Protein Expression and Purification. The general protein expression and purification protocol for UGT76G1 uses a combination of affinity and sizeexclusion chromatographies based on a previously published protocol (32). For production of SeMet-substituted protein, the pET-28a-UGT76G1 construct was transformed into E. coli BL21 (DE3) cells, which were grown to A 600 ∼ 0.8 at 37°C in M9 minimal media supplemented with SeMet containing 50 μg·mL −1 kanamycin (33).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, other GSL biosynthetic enzymes can utilize substrates derived from both methionine (the entry molecule for the aliphatic pathway) and tryptophan (the entry point for the indolic pathway), and include UGT74B1 (Grubb et al, 2004), SUR1 (Mikkelsen et al, 2004) and SOT16 (Klein and Papenbrock, 2009). Analyses of mutations in the isopropylmalate dehydrogenases and methylthioalkylmalate synthases, enzymes that are responsible for methionine chain elongations that precede the GSL core enzymes, revealed that single amino acid changes in the active sites can dramatically alter the substrate specificity of the enzymes (He et al, 2011;Lee et al, 2016;Kumar et al, 2019). Thus, although it has been demonstrated that FSH/GS-OX5 has a preference for longchain GSLs, catalyzing the conversion of methylthioalkyl GSLs to methylsulfinylalkyl GSLs (Li et al, 2008), the enzyme may also recognize unknown substrates, generating the product(s) that negatively influences growth and development.…”
Section: Substrate Promiscuity and Allosteric Interactions May Underpmentioning
confidence: 99%
“…The AtIPMDH2 Leu biosynthetic enzyme crystal structure with 3-isopropylmalate (3-IPM) revealed several binding interactions with the polar portion of the substrate [12]. The structure revealed that residues interacting with the polar groups of 3-IPM are conserved between all IPMDH enzymes (Figure 2B) [13].…”
Section: Gene Duplication and Changes In Substrate Specificity In Thementioning
confidence: 99%
“…This, combined with the similarity of the polar groups of 3-IPM and (3-(2′-methylthio)-ethylmalate, suggested that recognition of the side chain is responsible for substrate discrimination. There are no specific substrate-enzyme interactions between the 3-IPM aliphatic isopropyl side chain and the residues in the largely hydrophobic pocket in the active site (Figure 2B) [12,13]. Thus, the differences between the glucosinolate biosynthetic enzyme AtIPMDH1 and Leu IPMDH enzymes presumably are responsible for the difference in substrate specificity.…”
Section: Gene Duplication and Changes In Substrate Specificity In Thementioning
confidence: 99%
See 1 more Smart Citation